2019
DOI: 10.3390/coatings9080527
|View full text |Cite
|
Sign up to set email alerts
|

Triple Local Similarity Solutions of Darcy-Forchheimer Magnetohydrodynamic (MHD) Flow of Micropolar Nanofluid Over an Exponential Shrinking Surface: Stability Analysis

Abstract: In this paper, the MHD flow of a micropolar nanofluid on an exponential sheet in an Extended-Darcy-Forchheimer porous medium have been considered. Buongiorno’s model is considered in order to formulate a mathematical model with different boundary conditions. The governing partial differential equations (PDEs) of the nanofluid flow are changed into a third order non-linear quasi-ordinary differential equation (ODE), using the pseudo-similarity variable. The resultant ODEs of the boundary value problems (BVPs) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
9

Relationship

6
3

Authors

Journals

citations
Cited by 35 publications
(16 citation statements)
references
References 47 publications
0
16
0
Order By: Relevance
“…With existence of generation and absorption of heat, Jusoh et al [44] found multiple solutions and examined the stability of solutions. Triple solutions have been found for the micropolar nanofluid over shrinking surfaces by Lund et al [45]. The results of stability analysis exposed that only stable solution is the first one and the remaining two solutions are unstable.…”
Section: Introductionmentioning
confidence: 94%
“…With existence of generation and absorption of heat, Jusoh et al [44] found multiple solutions and examined the stability of solutions. Triple solutions have been found for the micropolar nanofluid over shrinking surfaces by Lund et al [45]. The results of stability analysis exposed that only stable solution is the first one and the remaining two solutions are unstable.…”
Section: Introductionmentioning
confidence: 94%
“…The above-mentioned linearized Equations (26)- (29) with boundary conditions (30) are solved by using BVP4c solver function in MATLAB software and found values of smallest eigenvalue ε. In order to find the smallest eigenvalues, there is to be relaxed one of the boundary conditions into initial condition as recommended by Harris et al [35] and Ali et al [36]. In this particular problem, there is relaxed the G 0 (η) → 0 as η → ∞ into G 0 (0) = 1.…”
Section: Stability Analysismentioning
confidence: 99%
“…Dual solutions, without performing the stability analysis, of micropolar nanofluid over the shrinking/stretching surface was found by Magodora et al [23] in the presence of thermal effect. Triple solutions of micropolar nanofluid over the shrinking surface with the effect of the velocity slip was obtained by Ali et al [24] in which they performed the analysis of stability in order to determine the stable solution. A few more related research articles of the micropolar fluid and nanofluid for the multiple solutions can be seen in References [25][26][27][28][29][30].…”
Section: Introductionmentioning
confidence: 99%